2014
DOI: 10.5539/res.v6n1p10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Levels of Development Based on the Human Development Index: A Comparison of Regression Models for Limited Dependent Variables

Abstract: This paper aims to examine the factors affecting the level of development of countries using various regression models for limited dependent variables including binary logit, probit and Tobit analyses. In this manner, the paper may suggest a road map for high developed countries to achieve very high developed levels. For this purpose, Human Development Indices of 84 countries were involved in the analysis with respect to nine independent variables. The results of the all regression models indicate that determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
3
16
0
7
Order By: Relevance
“…Singariya (2014) shows that infant mortality rate, the incidence of poverty and marriage below age eighteen an of important role in reducing the value of HDI. The primary focus on those countries is the education dimensions to reach the standards of top nations (Eren et al, 2014). Baseri and Kia (2008) suggest that it is crucial to improving the expenditure of physical and human investments to improve the quality of human life in a region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Singariya (2014) shows that infant mortality rate, the incidence of poverty and marriage below age eighteen an of important role in reducing the value of HDI. The primary focus on those countries is the education dimensions to reach the standards of top nations (Eren et al, 2014). Baseri and Kia (2008) suggest that it is crucial to improving the expenditure of physical and human investments to improve the quality of human life in a region.…”
Section: Resultsmentioning
confidence: 99%
“…Sarkar et al (2012) said that human development is one of the core considerations of a country's level of development. Human development is evidently about enlarging people's choices by shared natural resources (Eren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, however, indicated that such a relationship starts after a country attained a certain level of human development. Another study by Eren et al (2014) also examined the relationship between human development indicators. The study, which used various regression models, argued that life expectancy at birth, expected years of schooling, labor force participation rate, and GDP per capita have statistically significant effects on the level of human development.…”
Section: The Empirical Literature On the Link Between Good Governancementioning
confidence: 99%
“…For example, Sarkar, Sadeka, and Sikdar (2012) implies that the Human Development Index is the the principal of the world. Eren, Çelik, and Kubat. (2014) argue that the HD is evidently about augmenting an individual's decision by sharing natural assets.…”
Section: Introductionmentioning
confidence: 99%